Complicated bilateral fungal emphysematous pyelonephritis in a 55-year-old diabetic female: A case report and review of literature - Ensieh lotfali; sara Abolghasemi; Fatemehsadat Gatmirimotahhari; Mohammad Alizadeh; Zahra Arab-Mazar (Mazandaran University of Medical Sciences, 2018)
Background and Purpose: Emphysematous pyelonephritis (EPN) is a rare and serious disease causing acute renal failure. Diabetes is a major risk factor for this infection. Case report: Herein, we present the case of a 55-year-old female patient with diabetes and EPN caused by Candida albicans. The infection was complicated with endophthalmitis and endocarditis. The results of antifungal susceptibility analysis showed that C. albicans was resistant to fluconazole and susceptible to amphotericin-B and itraconazole. Infection could be controlled by amphotericin-B followed by itraconazole therapy, and the patient was discharged in good condition while receiving antifungal therapy. Conclusion: Complicated pyelonephritis with unusual microorganisms should be considered in patients with diabetes and urinary symptoms